(untitled) (Ustozlar uchun, 2025)
Another defining feature of modern English language teaching is the incorporation of intercultural competence into curricula. The ability to communicate effectively across cultures is considered an essential component of language learning in the twenty-first century. Modern approaches recognize that language and culture are inextricably connected, with effective communication hinging not only on linguistic proficiency but also on cultural awareness, sensitivity, and adaptability. Language educators are therefore tasked with introducing learners to the diverse cultural norms, values, and worldviews embedded within the English language. Such exposure encourages open-mindedness, empathy, and flexible communication strategies, equipping students to participate confidently in multicultural settings.